Dynamic and Asymmetric Dependences Between Chinese Yuan and Other Asia‐Pacific Currencies. Issue 8 (4th March 2013) - Lien, Donald; Wu, Chongfeng; Yang, Li; Zhou, Chunyang
Abstract This paper examines the dynamic dependence structure between Chinese Yuan and each of five other currencies in the Asia‐Pacific region on non‐deliverable forward contracts over the period of July 4, 2006 throughout August 31, 2011. Using the date that Lehman Brothers filed for bankruptcy as the starting date of financial crisis, we find that, before the crisis, the dependences between Chinese Yuan and four out of five other Asian pacific currencies under consideration are much stronger when Chinese Yuan against the U.S. dollar depreciates than when it appreciates. During the crisis, the asymmetric tail dependences still prevail with the magnitude of both upper and lower tail dependences as well as correlation increasing substantially. The dynamic and asymmetric dependence structure documented in this study has important implications for the investors in the region. © 2013 Wiley Periodicals, Inc. Jrl Fut Mark